Amperometric Metronidazole Sensor Based on the Supermolecular Recognition by Metalloporphyrin Incorporated In Carbon Paste Electrode - Ru-Qin Yu; Guo-Li Shen; Can-Cheng Guo; Xiao-Bing Zhang; Fu-Chun Gong (Sensors, 2003)
An amperometric metronidazole (MTZ) sensor using a glycosylated metalloporphyrin as a recognition element, which was incorporated in a carbon paste electrode, is reported. For the preparation of a MTZ-sensitive active material, 5, 10, 15, 20-tetrakis [2-(2, 3, 4, 6-tetraacetyl-β-D-glucopyranosyl)-1-O-phenyl]porphyrin (T(oglu) PPH2) and its Mn(III) complex MnT(o-glu)PPCl were synthesized from the reaction of pyrrole with ortho-acetylglycosylated benzaldehyde by Lindsay’s method. The MnT(oglu) PPCl-modified electrode showed excellent selectivity toward MTZ with respect to a number of interferents and exhibited stable response. The calibration graph obtained with the proposed sensor was linear over the range of 2.9×10-3-5.8×10-8 M/L, with a detection limit of 5.8×10-8 M/L for MTZ. Cyclic voltammetric measurements indicated that MnT(oglu) PPCl included in graphite-epoxy resin matrices could efficiently mediate electron transfer from the base electrode to MTZ causing a decrease of reduction potential for MTZ detection. The sensor could be regenerated by simply polishing with an alumina paper, with an excellent reproducibility (RSD=1.6%). The experimental conditions such as pH and applied working potential were optimized. The prepared sensor is applied for the determination of MTZ in pharmaceutical preparations and the results agreed with the values obtained by the pharmacopoeia method.